Automorphisms and Inner Automorphisms. (7th February 2016) - Jaber, Ameer; Yasein, Moh'D
Abstract : Let K be a field of characteristic not 2 and let A = A 0 + A 1 be central simple superalgebra over K, and let ⁎ be superinvolution on A . Our main purpose is to classify the group of automorphisms and inner automorphisms of ( A, ⁎ ) (i.e., commuting with ⁎ ) by using the classical theorem of Skolem-Noether. Also we study two examples of groups of automorphisms and inner automorphisms on even central simple superalgebras with superinvolutions.